LEARNING EFFECTIVENESS ON TRAINING BASED ON TEAMS LEARNING TOURNAMENT MODEL AND GOOGLE CLASSROOM APPLICATION - Firdos Mujahidin (Jurnal Perspektif, 2021)
The study aims to determine learning effectiveness on training based on the Teams Learning Tournament (TLT) model combined with Google Classroom application. The research method used is descriptive qualitative collected through observation and qualitative analysis. The research was conducted in 2020 held in Teachers’ Training of Basic Islamic School (MI) Pangandaran. The results showed that TLT learning model combined with Google Classroom application can manage learning effectively. The results showed that TLT learning models supported by the Google Classroom app can effectively manage learning, which can be seen from an increase in attitudes in liveliness of up to 100%, an average knowledge increase of 80.75% and the skills of participants can skillfully compose a predetermined learning product with an average skill score of 85.86. TraineesTLT learning model and Google Classroom application can also be separated to manage learning, but it will be more effective if those two are combined in learning.